MRI in liver cirrhosis - Alzoubi, Osama; Arar, Ahmad; Singh, Viraj; Erturk, Sukru M.; Mozes, Ferenc; Pavlides, Michael (Portal hypertension & cirrhosis (Print), 2022)
Liver magnetic resonance imaging (MRI) has seen a massive increase in its use over the last decades. Since its first description in the early 1980s, contrast‐enhanced MRI is now the gold standard for the diagnosis of hepatocellular cancer in patients with liver cirrhosis. Techniques like magnetic resonance (MR) elastography and combinations of multiple MR parameters in single scanning protocols are now available and these are opening new possibilities for the assessment of multiple aspects of disease in patients with liver cirrhosis. In this narrative review, we provide an overview of the use of MRI in patients with cirrhosis for the diagnosis of and screening for liver cancer, for the diagnosis of cirrhosis and prediction of long‐term outcomes, and for the evaluation of portal hypertension. With the multitude of techniques now available and the number of cirrhosis aspects that can be assessed by single scans make the study and application of MRI an attractive target in the search for a technique for use in this group of patients that often have to attend for multiple appointments and multiple tests, including invasive investigations. Magnetic resonance imaging (MRI) with gadolinium contrast is the current gold standard for the diagnosis of hepatocellular cancer (HCC) in patients with liver cirrhosis (top panel). Recent developments have seen new applications of magnetic resonance (MR) in more indications including screening for HCC, diagnosis of cirrhosis, risk stratification for future decompensation, and portal hypertension assessment (middle panel). It is possible that in the future that multiple MR modalities will be combined into single scanning sessions to provide data for multiple indications (bottom panel). Key points Contrast‐enhanced magnetic resonance imaging is the current gold standard for diagnosis of hepatocellular cancer (HCC) in patients with cirrhosis. Magnetic resonance techniques including elastography and Liver MultiScan (Perspectum Ltd.) have recently seen applications in diagnosis and risk stratification of cirrhosis, screening for HCC and ass.